Antimicrobial Resistance: Identifying the Major Conflicts of Interest and Way Forward - Sharma, Samridhi; Govender, Kemesha; Nagaraju, Kiran; Chhetri, Pratik; Menze, Thandiwe; Srinivas, Sunitha C (Indian Journal of Pharmacy Practice)
“We find ourselves on the brink of a post-antibiotic era” – Department of Health Republic of South Africa, 2015.1 According to the World Health Organisation (WHO), antimicrobial resistance (AMR) is a global threat to public health.2 AMR causes around 700 000 deaths every year, and is projected to lead to 10 million deaths annually by 2050.